(untitled) (Intent Research Scientific Journal, 2026)
This article discusses the fact that a native language teacher can achieve effective results only by combining the competency-based, communicative, innovative, integrative, and personality-oriented approaches in linguodidactic training. It is reported that these approaches shape the future teacher as a creative, independent thinker and a technically competent specialist who meets the requirements of modern education.